2002
DOI: 10.1016/s1074-5521(02)00236-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nucleotide Exchange in Saccharomyces cerevisiae Directed by Short Oligonucleotides Containing Locked Nucleic Acids

Abstract: Locked nucleic acids (LNAs) are novel base modifications containing a methylene bridge uniting the 2'-oxygen and the 4'-carbon. In this study, LNA-modified single-stranded molecules directed the repair of single base mutations in a yeast chromosomal gene. Using a genetic assay involving a mutant hygromycin-resistance gene, correction of point and frameshift mutations was facilitated by vectors containing an LNA residue on each terminus. Increasing the number of LNA bases on each terminus reduced the correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…This assay has previously enabled an investigation of optimal targeting vectors and proteins essential for the pairing phase of the TNE reaction (Liu et al, 2001;Liu et al, 2002a;Liu et al, 2002b;Liu et al, 2003;Liu et al, 2004;Parekh-Olmedo et al, 2002). Studies have shown that an MSSO is capable of directing the repair of a chromosomal insertion mutation, but the repair of a chromosomal deletion mutation was not investigated.…”
Section: Modified Single-stranded Oligonucleotides Direct the Repair mentioning
confidence: 99%
“…This assay has previously enabled an investigation of optimal targeting vectors and proteins essential for the pairing phase of the TNE reaction (Liu et al, 2001;Liu et al, 2002a;Liu et al, 2002b;Liu et al, 2003;Liu et al, 2004;Parekh-Olmedo et al, 2002). Studies have shown that an MSSO is capable of directing the repair of a chromosomal insertion mutation, but the repair of a chromosomal deletion mutation was not investigated.…”
Section: Modified Single-stranded Oligonucleotides Direct the Repair mentioning
confidence: 99%
“…Hyg3S/74NT is a 74-mer that is specific for binding to the nontranscribed strand and contains three terminal phosphorothioate linkages. 8,11,12 Also shown is the target sequence of the mutant, which contains a TAG stop codon. Figure 2c illustrates the structure of the b-globin YAC and nucleotides targeted for editing are specified.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, BAC modifications must be conducted in a specially engineered strain, while our method can be used in essentially any genetic background, targeting either a plasmid or a chromosome. 8,11,12 More importantly, BACs have a restricted length of foreign DNA (p300 kb) capable of being stably maintained, while YACs can hold up to 2 Mb (see, for review, Huxley 19 ). Therefore, YACs enable targeting of introns and regulatory as well as coding regions, and could reveal interactions between genes linked too loosely to be present on a single BAC or PAC.…”
Section: Aj Van Brabant Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…MSOs that are 70 to 80 bases long appear to be optimal for TNE on both episomes and chromosomes (12). Alternative modifications, such as locked nucleic acid residues, can also protect against nuclease digestion while high levels of activity are maintained (20). Locked nucleic acid residues may eventually prove to be useful since they have low levels of cellular toxicity, especially in mammalian cells (27).…”
mentioning
confidence: 99%